Breaking the news how the media undermine American democracy - Fallows, James (New York Vintage Books, 1997)
Why do Americans mistrust the news media? It may be because show like "The McLaughlin Group" reduce participating journalists to so many shouting heads. Or because, increasingly, the profession treats issues as complex as health-care reform and foreign policy as exercises in political gamesmanship. Or because muckrackers have given way to "buckrakers" who command huge fees lecturing to the very interest groups they are supposed to cover.

These are just a few of the arguments that have made Breaking the News so controversial and so widely acclaimed. Drawing on his own experience as a National Book Award-winning journalist--and on the gaffes of colleagues from George Will to Cokie Roberts--Fallows shows why the media have not only lost our respect but alienated us from our public life. Moving from rigorous analysis to concrete proposals, the result is a devastating critique that is indispensable for anyone who makes the news--and anyone who reads or watches it.
Includes bibliographical references (pages 291-311) and index (315-337).
Donated by Ms. Triccie Cantero, U.P. Samaskom 84.1.
Keywords: Press and politics -- United States; Journalism -- Objectivity -- United States; Mass media -- Objectivity -- United States